First record of Todea (Osmundaceae) in South America, from the early Eocene paleorainforests of Laguna del Hunco (Patagonia, Argentina). Issue 9 (1st September 2013) - Carvalho, Mónica R.; Wilf, Peter; Hermsen, Elizabeth J.; Gandolfo, Maria A.; Cúneo, N. Rubén; Johnson, Kirk R.
Abstract : Premise of the Study: The early Eocene Laguna del Hunco caldera‐lake paleoflora (ca. 52 Ma) from Chubut Province, Argentina, is notably diverse and includes many conifer and angiosperm lineages that are extinct in South America but extant in Australasian rainforests. No ferns have been previously described from Laguna del Hunco. We describe and interpret a new species of fossil Osmundaceae based on fertile and sterile pinnae. Methods: The fossil specimens were compared with other extant and fossil Osmundaceae based on living and herbarium material and published descriptions. A morphological matrix based on 29 characters was constructed for 17 living species in Osmundaceae, four species assigned to the fossil genus Todites, and the new fossil species. Phylogenetic analyses were conducted under parsimony using morphology and total evidence matrices. Key Results: Both the new fossil and the Todites species were consistently resolved within the leptopteroid clade of Osmundaceae, and the new species resolved in a clade with the two living Todea species, which are now restricted to Australia, New Guinea, New Zealand, and southern Africa. Conclusions: Todea amissa sp. nov. is the first record of Todea, living or fossil, in South America and only the second fossil record worldwide. The distribution of extant Todea on Gondwanan continents other than South America is broadly shared with other taxa from Laguna del Hunco, further indicating that a large component of this flora represents a Gondwanic biome that is no longer found on the South American continent.